Acute and Chronic Dose Response Effect of Methylphenidate on Ventral Tegmental Area Neurons Correlated With Animal Behavior - Jones, Zachary (J Neural Transm (Vienna), 2013)
Methylphenidate (MPD) is used to treat ADHD and as a cognitive enhancement and recreationally. MPD's effects are not fully understood. One of the sites of psychostimulant action is the ventral tegmental area (VTA). The VTA neuronal activity was recorded from freely behaving rats using a wireless system. 51 animals were divided into groups: saline, 0.6, 2.5, and 10.0 mg/kg MPD. The same repetitive MPD dose can elicit either behavioral sensitization or tolerance, thus the evaluation of the VTA neuronal activity was based on the animals’ behavioral response to chronic MPD exposure: animals exhibiting behavioral tolerance or sensitization. Acute MPD elicits dose related increases in behavioral activity. About half of the animals exhibited behavioral sensitization or tolerance to each of the MPD doses. 361 units were recorded from the VTA and exhibited similar spike shape on experimental day 1 (ED1) and on ED10. 71%, 84%, and 79% of VTA units responded to acute 0.6, 2.5, and 10.0 mg/kg MPD respectively. The neuronal baseline activity at ED10 was significantly modified in 94%, 95%, and 100% of VTA units following 0.6, 2.5 and 10.0 mg/kg MPD respectively. Following chronic MPD exposure, 91%, 98%, and 100% exhibit either electrophysiological tolerance or sensitization of 0.6, 2.6, or 10.0 mg/kg MPD respectively. In conclusion, the chronic administration of the same dose of MPD caused some animals to exhibit behavioral sensitization and other animals to exhibit tolerance. The VTA units recorded from animals exhibiting behavioral sensitization responded significantly differently to MPD from animals that exhibited behavioral tolerance.